Implementasi Service Quality Dalam Pelayanan Perpustakaan di Dinas Perpustakaan Dan Arsip Kabupaten Deli Serdang - Sopa Rosa Lubis; Achiriah Achiriah; Abdi Mubarak Syam (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is about the implementation of service quality in library services at the Library and Archives Office of Deli Serdang Regency. In investigating the implementation of service quality in library services at the Library and Archives Office of Deli Serdang Regency, researchers used descriptive qualitative research. Data collection occurred in a natural environment. Positive recognition of quick responses and guidance from library staff created opportunities to encourage positive behavior. Lack of time and internet connectivity, indicating potential improvements in terms of technical infrastructure. The findings highlight the importance of continuous evaluation of library services. The extent to which remedial action is taken in response to evaluation results can have a positive impact on user satisfaction. By implementing such effects, the Deli Serdang library and archives service will be able to further improve the quality of its services and ensure its patrons' needs are met thereby increasing user satisfaction. The department has one librarian and 17 library technology staff members. Additional librarians are needed, especially in the IT department. Understanding the Concept of Service Quality and Visitor Satisfaction: Service Quality of Deli Serdang Library and Archives. Service is the key to improving visitor satisfaction. Library management is an important component of service success. Utilization of various library services includes.